Hubungan Antara Populasi Kutu Kebul (Bemisia tabaci) (Gennadius) ( Hemiptera : Aleyrodidae) dengan Insiden Penyakit Kuning pada Tanaman Tomat (Solanum Lycopersicum Mill.) di Dusun Marga Tengah, Desa Kerta, Kecamatan Payangan, Bali - NARENDRA, ANAK AGUNG GDE AGUNG; PHABIOLA, TRISNA AGUNG; YULIADHI, KETUT AYU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.3, Juli 2017, 2017)
The Relationship Between Population of Whiteflies (Bemisia tabaci) (Genemadius) (Hemiptera : Aleyrodidae) with Incident of Yellow Disease on Tomato Plant (Solanum lycopersicum Mill.) in Dusun Marga Tengah, Kerta Village, Payangan District, Bali The disease of tomato is namely yellow disease that is caused by a Geminivirus from species Tomato Yellow Leaf Curl Virus (TYLCV) . That virus can be propagated through the vector that is Bemisia tabaci. This study aimed to know the relationship between population of Bemisia tabaci (Genemadius) (Hemipteraaleyrodidae) with incident of yellow disease on tomato plant (Solanum Lycopersicum Mill.) This study is located at the center of tomato cultivation in Dusun Marga Tengah, Kerta Village, Payangan, Bali from December 2016 to February 2017. This study observe the number of nymphs Bemisia tabaci on tomato plants as sample that choosen and observed the incidence of disease in tomato plant area. Relationship between yellow disease incidence with population of Bemisia tabaci is analyzed by a linear regression model. The results showed that the incidence of yellow disease in tomato plants correlated positively and significant with the increase of vector insect population Bemisia tabaci that is 87,37%.